2022
DOI: 10.1136/bcr-2021-248013
|View full text |Cite
|
Sign up to set email alerts
|

Benzocaine-induced methaemoglobinaemia in an adolescent with sepsis

Abstract: Methaemoglobinaemia is a potentially life-threatening condition characterised by hypoxaemia, cyanosis, pallor, fatigue, metabolic acidosis, headache and in severe cases, coma or death. Topical anaesthetics have been reported to cause methaemoglobinaemia. Topical benzocaine was specifically implicated in roughly 66% of anesthetic-induced methaemoglobinaemia cases in a large systematic review in adults. This complication has occurred often in adult patients with pre-existing comorbidities resulting in diminished… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…However, pediatric exposure to such large concentrations may result in methemoglobinemia, which is characterized by cyanosis, hypoxia and dyspnea that do not improve with oxygen administration. Other adverse effects include hypotension, bradycardia, cardiac arrest, seizures, drowsiness, dizziness, edema, and allergic reactions [9,13,16,17,18] . In a study by Wang on benzocaine or benzocaine combined with tetracaine, it was concluded that when applied to the cheek mucosa, it does not induce clinically significant elevations in methemoglobin levels.…”
Section: Adverse Effectsmentioning
confidence: 99%
“…However, pediatric exposure to such large concentrations may result in methemoglobinemia, which is characterized by cyanosis, hypoxia and dyspnea that do not improve with oxygen administration. Other adverse effects include hypotension, bradycardia, cardiac arrest, seizures, drowsiness, dizziness, edema, and allergic reactions [9,13,16,17,18] . In a study by Wang on benzocaine or benzocaine combined with tetracaine, it was concluded that when applied to the cheek mucosa, it does not induce clinically significant elevations in methemoglobin levels.…”
Section: Adverse Effectsmentioning
confidence: 99%